2014
DOI: 10.1111/head.12425
|View full text |Cite
|
Sign up to set email alerts
|

Giant Cell Arteritis

Abstract: Giant cell arteritis (GCA) is a medium and large-vessel vasculitis, which is an important cause of secondary headache in older adults. While GCA has a classic presentation occurring after the age of 50, atypical presentations (eg, fever of unknown origin, cough, low or normal erythrocyte sedimentation rate) may lead to a delay in diagnosis. The topography of vascular involvement has implications for disease-related complications, which can result in neurologic disease at multiple levels of the nervous system. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 160 publications
0
46
0
1
Order By: Relevance
“…This fact is supported by a literature review on previously reported cases [1]. Therefore, GCA should be presumed as a possibility in all elderly patients more than 50 years of age who present with a new-onset headache and vision changes [2]. A high clinical suspicion should be maintained in such individuals while understanding the subtle clinical differences in GCA and carotid atherosclerosis such as vascular distribution and ophthalmological findings.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…This fact is supported by a literature review on previously reported cases [1]. Therefore, GCA should be presumed as a possibility in all elderly patients more than 50 years of age who present with a new-onset headache and vision changes [2]. A high clinical suspicion should be maintained in such individuals while understanding the subtle clinical differences in GCA and carotid atherosclerosis such as vascular distribution and ophthalmological findings.…”
Section: Introductionmentioning
confidence: 84%
“…However, non-atherosclerotic carotid disease can have similar symptoms with rather uncommon causes such as giant cell arteritis (GCA) [2,4]. …”
Section: Discussionmentioning
confidence: 99%
“…Incidence increases with age as 15-25 cases per 100,000 have been reported in individuals aged more than 50 yrs [24] and it increased to 44.7 per 100,000 in individuals aged more than 80 yrs [25]. The scandinavian population has been shown to have a higher incidence rate as compared to any other population [26].…”
Section: Giant Cell (Temporal) Arteritismentioning
confidence: 98%
“…These symptoms can be seen simultaneously in both eyes or in progression with one eye being affected before the other. Vision loss is the most prevalent complication of GCA and makes this condition an emergency [26]. Other neurologic symptoms include stroke, dementia and neuropathy [27].…”
Section: Giant Cell (Temporal) Arteritismentioning
confidence: 99%
“…Giant cell arteritis (GCA) is one of the most important neurological diseases because of its potential to cause sudden and irreversible blindness and other central nervous system complications, making prompt diagnosis and immediate initiation of corticosteroid therapy a medical emergency [30]. GCA is characterized pathologically by inflammation in and damage to the vessel wall of the temporal arteries (TAs) [31,32].…”
Section: Giant Cell Arteritismentioning
confidence: 99%